The Influence of Visualization in Book Content on Language Processing and Memory - Adi, Dian Prasetyo; Avenida, Quinta; Sugiarti, Tati; Lianisyah, Ulfah Yanuar; Rudiansyah (International Journal of Science and Society, 2024)
This study explored the effects of visualization and phonetic processing on comprehension and memory retention in learning Mandarin as a second language. Through an experiment involving three conditions: pinyin, black-and-white pictures, and colored pictures, the study evaluated participants’ accuracy and reaction time in completing visual and phonetic-based tasks. The results showed that visual cues, especially colored pictures, increased response accuracy and decreased reaction time compared to pinyin and black-and-white pictures. These findings suggest that visualization not only aids vocabulary recall but also facilitates faster cognitive processing, potentially reducing students’ cognitive load. Implications for Mandarin teaching include the importance of using appropriate visual teaching materials to support learning and memory retention at the beginner level. These results contribute to the growing body of evidence supporting the effectiveness of multimodal learning and the importance of tailoring teaching methods to learners’ cognitive characteristics.